2023
DOI: 10.3390/antiox12051021
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Spirulina to Craft Beer: Evaluation of the Effects on Volatile Flavor Profile and Cytoprotective Properties

Abstract: SPME-GC-MS and PTR-ToF-MS techniques were applied to describe the content of volatile flavor compounds in a craft beer before and after adding spirulina. The obtained results showed that the volatile profile of the two beer samples differed. Furthermore, to chemically characterize biomass spirulina, a derivatization reaction followed by GC-MS analysis was performed, highlighting a high content of molecules belonging to different chemical classes, such as sugars, fatty acids and carboxylic acids. A spectrophoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Confocal microscopy of yeast cells enabled the examination of riboflavin autofluorescence, which in turn elucidated essential information regarding the cofactor riboflavin [ 22 , 23 ]. Several factors, such as pH and the presence of other molecules, can affect riboflavin fluorescence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Confocal microscopy of yeast cells enabled the examination of riboflavin autofluorescence, which in turn elucidated essential information regarding the cofactor riboflavin [ 22 , 23 ]. Several factors, such as pH and the presence of other molecules, can affect riboflavin fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…A SPME device from Supelco (Bellefonte, PA, USA) with 1 cm fiber coated with 50/30 μm DVB/CAR/PDMS (divinylbenzene/carboxen/polydimethylsiloxane) was chosen to extract the components. The operative conditions followed Taiti et al [ 23 ]. Component desorption was ensured by inserting the fiber directly into the GC injector maintained at 250 °C in splitless mode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, the effects of adding spirulina to craft beer were evaluated. The results demonstrated that spirulina, in addition to modifying the content of compound esters, improved the cytoprotective properties of beer towards tBOOH-induced oxidative damage in H69 cells and reduced intracellular oxidative stress [11].…”
Section: Introductionmentioning
confidence: 95%
“…To describe the chemical composition of spirulina, a derivatization reaction was performed according to Taiti et al [11]. The analysis was performed using the same apparatus GC-FID/GC-MS and the same capillary column (Varian Factor Four VF-Agilent, Santa Clara, CA, USA).…”
Section: Gc-ms Analysis Of Spirulina After the Derivatization Reactionmentioning
confidence: 99%